Penggunaan Media Animasi pada Pembelajaran Bahasa Indonesia dalam Meningkatkan Hasil Belajar Siswa Kelas I SDIT Bunayya Pekanbaru - Anisa Octavia; Deprizon Deprizon; Wismanto Wismanto; Radhiyatul Fitri; Salman Salman; Sakban Sakban (Institut Nalanda, 2024)
This research is based on the low learning outcomes of students in Indonesian language subjects because students feel bored, fed up with learning carried out using the lecture method so that students are not interested in participating in learning. This research aims to improve the learning outcomes of class I students at SDIT Bunayya Pekanbaru in Indonesian language subjects by using animation media in the learning process. This research is classroom action research (PTK). The subjects in this research were class I students at SDIT Bunayya Pekanbaru, totaling 25 students. Meanwhile, the object of this research is the use of animation media in Indonesian language learning to improve the learning outcomes of class I students at SDIT Bunayya Pekanbaru. This research was carried out in two cycles, each cycle was carried out over two meetings. Each cycle consists of four stages, namely planning, implementation, observation and reflection. The results of research on the use of animation media in Indonesian language learning in improving the learning outcomes of class I students at SDIT Bunayya Pekanbaru are that in the first cycle, 82.25% of teacher activities were in the good category, 83.2% of student learning outcomes were in the good category. In cycle II, the results of using animation media increased, 96.25% of teacher activities were in the very good category, 96% of student learning outcomes were in the very good category. The results of this research show that the use of animation media in Indonesian language learning improves the learning outcomes of class I students at SDIT Bunayya Pekanbaru improves student learning outcomes.